2022
DOI: 10.48550/arxiv.2206.14537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral clustering of Markov chain transition matrices with complex eigenvalues

Abstract: The Robust Perron Cluster Analysis (PCCA+) has become a popular algorithm for coarsegraining transition matrices of nearly decomposable Markov chains with transition states. Though originally developed for reversible Markov chains, it has been shown previously that PCCA+ can also be applied to cluster non-reversible Markov chains. However, the algorithm was implemented by assuming the dominant (target) eigenvalues to be real numbers. Therefore, the generalized Robust Perron Cluster Analysis (G-PCCA+) has recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…(ii) As in Li et al (2021), we applied a PCCA type algorithm to partition the state space into fewer metastable states. The algorithm, as described in Frank et al (2022), was extended to also deal with irreversible Markov chains, which makes it applicable to a wider range of biological processes. (iii) Instead of applying TPT on all micro-states as in Li et al (2021), we adapted a coarse-grained version of TPT only between the identified phenotypes, which is less computational intensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) As in Li et al (2021), we applied a PCCA type algorithm to partition the state space into fewer metastable states. The algorithm, as described in Frank et al (2022), was extended to also deal with irreversible Markov chains, which makes it applicable to a wider range of biological processes. (iii) Instead of applying TPT on all micro-states as in Li et al (2021), we adapted a coarse-grained version of TPT only between the identified phenotypes, which is less computational intensive.…”
Section: Discussionmentioning
confidence: 99%
“…The Matlab code (macro-tpt Frank and Röblitz ( 2022)) for all presented cases is available on GitHub (https://github.com/a-sfrank/macro-tpt.git). The cPCCA+ Matlab code, as described in Frank et al (2022), was downloaded from GitHub (https://github.com/sroeblitz/cPCCA.git), adapted and integrated into our implementation.…”
Section: Credit Authorship Contribution Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Accession codes The Matlab codes for all presented cases are available on GitHub (https://github.com/a-sfrank/ macro-tpt.git). The cPCCA+ Matlab code, as described in 34 , was downloaded from GitHub (https://github.com/ sroeblitz/cPCCA.git), adapted and integrated into our implementation.…”
Section: Author Contributions Statementmentioning
confidence: 99%
“…This leads to the maximization problem max ∈A ( ), with ( ) = which is then solved using an efficient optimization algorithm based on the Schur reordering algorithm that takes the side constraints (4.21) and (4.22) into account by projection techniques; see Röblitz andWeber (2013) andSikorski (2015) for details. Moreover, there are several extensions and variants, for example to take into account specifics of non-reversible cases; seeFrank et al (2022).…”
mentioning
confidence: 99%